Bilateral Thalamic and Right Fronto-temporo-parietal Gliomas in a 4 Years Old Child Diagnosed by Magnetic Resonance Imaging - Sharaf, Ahmed Fathy (J Radiol Case Rep, 2016)
We report the neuroimaging findings of a 4-year-old girl with biopsy-proven bilateral thalamic and right fronto-temporo-parietal cortical gliomas, which are uncommon tumours involving the central nervous system. Despite their benignity, the prognosis is usually poor because of involvement of the thalamic nuclei and difficulty in surgical excision. These lesions have limited differential diagnoses that include metabolic, toxic, infective, vascular and neoplastic. Imaging characteristics on conventional Magnetic Resonance (MR), Magnetic Resonance Spectroscopy (MRS) and Diffusion tensor imaging (DTI) can further narrow the differential diagnosis and also provide additional information regarding the degree of involvement of adjacent brain tissue and white matter tracts around the lesions.